Exploring the effects of extreme events on cereal cropping systems in the Ganga River basin, Haryana - Dubey, Swatantra Kumar; Veettil, Prakashan Chellattan; Patil, Vikram; Deb, Proloy; Kumar, Virender (IWA Publishing, 2024)
Recent studies have highlighted the profound impact of global warming on climate patterns worldwide, but few have specifically addressed its consequences for crop yields. This study aims to bridge that gap by examining the trends of extreme events and their effects on agriculture in adjacent Ganga River Basin Haryana districts from 1981 to 2020, focusing on the Expert Team on Climate Change Detection, Monitoring and Indices. The study area experienced increasing mean maximum and minimum temperatures, raising drought concerns, especially in Sonipat and Panipat districts. Drought indices showed prolonged events in these areas, contrasting with shifting wet-dry patterns in Yamuna Nagar and fluctuating conditions in Karnal. An analysis from 1998 to 2020 revealed intricate relationships between climate factors and rice, wheat, and pearl millet production, with rising temperatures significantly impacting crop yields. Notably, both mean maximum and minimum temperatures have increased, with a significant daytime and nighttime warming trend. Extreme maximum temperature and diurnal temperature range indices were found to negatively impact crop yields, whereas precipitation extremes demonstrated positive correlations with yield outcomes. Collaborative efforts between policymakers and farmers to integrate climate-resilient practices and continuous monitoring are crucial for ensuring food security and sustainable farming amidst climate variability.